Kinetics of Esterification of 2-Keto-L-Gulonic Acid with Methanol Catalyzed by Cation Exchange Resin - 许保云 郑学明 张卫江 张雪梅 张智勇 尚会建 (Transactions of Tianjin University, 2008)
The kinetics of esterification of 2-keto-L-gulonic acid with methanol in the liquid phase catalyzed by cation exchange resin, D001, was studied. The experiments were carried out in a stirred batch reactor at 318, 323, 328, 333, 338, 341 K under atmospheric pressure, It is found that the speed of rotating rate has no effect on the esterification rate in the range of 300-500 r/min and the effect of internal mass transfer resistance is not obvious. The effects of temperature and catalyst loading on the reaction rate were researched under the condition of eliminating the effect of diffusion. The rate was found to increase with the increase of the temperature and catalyst loading. The experimental data were correlated with a kinetic model based on the pseudo- homogeneous catalysis, The kinetic equation for describing the reaction catalyzed by cation exchange resin was developed, The experimental data are in good agreement with the model